A prática de atividades físicas e o uso de recursos ergogênicos por Policiais Militares da 5° CIPM de Tocantinópolis - TO, antes e durante a pandemia da COVID-19 - Rodrigo Ferreira, Brandão (Universidade Federal do Tocantins, 2022)
The study was carried out with the following objectives: to verify the practice of physical exercises and the use of ergogenic resources by military police officers of the 5th CIPM